Rational Engineering of p‐n Heterogeneous ZnS/SnO2 Quantum Dots with Fast Ion Kinetics for Superior Li/Na‐Ion Battery - Zhan, Guang‐Hao; Liao, Wen‐Hua; Hu, Qian‐Qian; Wu, Xiao‐Hui; Huang, Xiao‐Ying (Small (Weinheim an der Bergstrasse, Germany), 2023)
Constructing heterogeneous nanostructures is an efficient strategy to improve the electrical and ionic conductivity of metal chalcogenide‐based anodes. Herein, ZnS/SnO2 quantum dots (QDs) as p‐n heterojunctions that are uniformly anchored to reduced graphene oxides (ZnS‐SnO2@rGO) are designed and engineered. Combining the merits of fast electron transport via the internal electric field and a greatly shortened Li/Na ion diffusion pathway in the ZnS/SnO2 QDs (3–5 nm), along with the excellent electrical conductivity and good structural stability provided by the rGO matrix, the ZnS‐SnO2@rGO anode exhibits enhanced electronic and ionic conductivity, which can be proved by both experiments and theoretical calculations. Consequently, the ZnS‐SnO2@rGO anode shows a significantly improved rate performance that simple counterpart composite anodes cannot achieve. Specifically, high reversible specific capacities are achieved for both lithium‐ion battery (551 mA h g−1 at 5.0 A g−1, 670 mA h g−1 at 3.0 A g−1 after 1400 cycles) and sodium‐ion battery (334 mA h g−1 at 5.0 A g−1, 313 mA h g−1 at 1.0 A g−1 after 400 cycles). Thus, this strategy to build semiconductor metal sulfides/metal oxide heterostructures at the atomic scale may inspire the rational design of metal compounds for high‐performance battery applications. The interface engineering technology of metal ionic liquid precursors is applied to construct ZnS/SnO2 quantum dots as p‐n heterojunctions, which shows excellent lithium‐ and sodium‐ storage performance and excellent long‐term cycle stability. Such a heterogeneous engineering strategy for nano‐metal sulfide/metal oxide heterojunctions can be extended to other electrodes for advanced rechargeable batteries .